A mixed method research study on pre-service primary school teachers’ mathematical disposition - Albay, Aybegum; Cetin, Hatice (Journal on Mathematics Education, 2023)
This is a comprehensive study aiming to examine pre-service primary school teachers’ (PPST) mathematical disposition levels in terms of various variables, and to explain the results thoroughly. It employed the explanatory sequential design among the mixed method research designs. The data were collected through Mathematics Dispositional Functions Inventory (MDFI) and semi-structured interviews. The participants consisted of 361 PPSTs in the quantitative phase, and six PPSTs in the qualitative phase. Quantitative data were analyzed with descriptive and inferential statistics, while qualitative data were analyzed with descriptive analysis. The PPSTs’ mathematical disposition levels did not differ significantly in terms of grade level, high school type, area of education at high school and ability area variables; however, their scores in the attitude toward mathematics lesson factor of MDFI differed significantly in terms of area of education at high school and ability area variables. There were significant, positive, and low-level relationships between PPSTs’ mathematical disposition levels and their levels of mathematics learning experience in primary, middle and high schools, and their perception level of mathematics teaching efficacy. The PPSTs’ scores in attitude toward mathematics lesson factor related to ability area were consistent with their statements in the interviews. The quantitative analysis results regarding mathematics learning experience levels and mathematics teaching efficacy perception levels, defined as continuous variables, overlapped with the qualitative analysis results.